The symmetry regained. - Lo, Tien-Chun (Analysis, 2024)
Collin (2022) attempts to break the symmetry between the modal ontological argument for the existence of God and the reverse modal ontological argument against the existence of God by drawing on some Kripkean lessons about a posteriori necessity. He argues that there is an undercutting defeater for taking God's non-existence to be possible. In this paper, I reply that taking the Kripkean considerations about a posteriori necessity into account does not help break the symmetry. For we can argue in a similar way that there is an undercutting defeater for taking God's existence to be possible.